2011
DOI: 10.1016/j.watres.2010.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tetracycline resistance on the transport of manure-derived Escherichia coli in saturated porous media

Abstract: In this research, tetracycline resistant (tet R ) and tetracycline susceptible (tet S ) Escherichia coli isolates were retrieved from dairy manure and the influence of tetracycline resistance on the transport of E. coli in saturated porous media was investigated through laboratory column transport experiments. Experimental results showed that tet R E. coli strains had higher mobility than the tet S strains in saturated porous media. Measurements of cell surface properties suggested that tet R E. coli strains e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 66 publications
(91 reference statements)
6
35
0
Order By: Relevance
“…Our previous results showed that the deposition rate coefficients calculated using Eq. 1 were similar to those estimated using mathematical models that consider the blocking effects of retained bacterial cells on the surface of the solid matrix (i.e., the Langmuir type of model; Walczak et al 2011). …”
Section: Column Transport Experimentssupporting
confidence: 70%
“…Our previous results showed that the deposition rate coefficients calculated using Eq. 1 were similar to those estimated using mathematical models that consider the blocking effects of retained bacterial cells on the surface of the solid matrix (i.e., the Langmuir type of model; Walczak et al 2011). …”
Section: Column Transport Experimentssupporting
confidence: 70%
“…It is well known that E. coli K12 cells lack O-antigen (the repeating polysaccharide component of LPS) [54], as a result, the values obtained in this research (2–6 μg/10 8 cells) were significantly lower than those measured for many environmental E. coli strains [25, 34]. …”
Section: Resultsmentioning
confidence: 60%
“…The deposition rate coefficients under clean-bed conditions ( K d , min −1 ) can be determined from the breakthrough concentration of bacterial cells using the following equation [3234]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wellknown example is from the field of automotive applications, more precisely the catalytic converter (Shuai and Wang, 2004). Porous media are also used in other fields of engineering, in waste water treatment as a filter (Janzen et al, 2009), in bacteria transport in connection with groundwater decontamination (Walczak et al, 2011) and in the food industry (Braeken et al, 2004).…”
Section: Introductionmentioning
confidence: 99%